Humaria Laevispora, a New Cryptic Species of Pezizales (Pyronemataceae, Ascomycetes) Based On Morphoanatomical and Phylogenetic Analysis From Pakistan (Bangladesh Journal of Plant Taxonomy, 2021)
In order to explore the biodiversity of mushrooms from Pakistan, authors come across a new Humaria sp. associated with Pinus wallichiana from Pakistan’s part of Himalayan moist temperate forests. Morpho-anatomical and phylogenetic characterization were used to elucidate their taxonomic affinities. Morphological and phylogenetic analysis confirms that it is a new species of Humaria. Humaria laevispora is subsequently described in detail and compared to closely related taxa Humaria hemisphaerica. The analysis also reveals that epigeous Humaria sp. is sister to hypogeous Genea spp. reflecting epigeous habit in Humaria a derived condition.Bangladesh J. Plant Taxon. 28(2): 379-384, 2021 (December)